Upaya PLN Dalam Mengatasi Pencurian Aliran Listrik (Studi Kasus Di Kecamatan Siak Hulu Kabupaten Kampar): Universitas Islam Riau - Riky Novarizal; Basyaruddin Basyaruddin (SISI LAIN REALITA, 2018)
This study aims to find out what are the factors causing the phenomenon of electricity theft in the District of Siak Hulu Kampar Regency. This type of research is descriptive and the method I use is qualitative. The location of the research in this study will be the author to do in the District of Siak Hulu Kampar Regency. The reason the author chose this location is because this location is a place where people steal electricity. In this study the key informants were PLN officials, especially P2TL. Data collection techniques that are usually carried out include observation, interviews, and documentation. The data analysis technique of this study will use descriptive analysis of qualitative data. Based on the results of the study, it was found that the economy was one of the reasons informants committed theft of electricity. The low level of public knowledge about the effects of flow theft and many sources is a factor in electricity theft. The reason is the lack of awareness of consumers or customers, besides that the average consumer wants a small or low electricity payment but wants to use as much power as possible. In addition, PLN has attempted to carry out various methods such as socialization of the community or residents who do not understand the theft of electricity, causing the informant to lose direction and decide to steal electricity and to misuse electricity for things prohibited by PLN regulations even in law. Indonesian.